Efektivitas Metode Role Playing untuk Meningkatkan Achievment Motivation Siswa Kelas X MA Manbail Futuh - Andhika Fatchur Widyanto; Sani Latifatul Khilmina (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to examine the effectiveness of the role-playing method in improving the achievement motivation of tenth-grade students at MA Manbail Futuh. A quantitative approach with a quasi-experimental design, specifically the Non-Equivalent Control Group Design, was employed, involving 40 students divided into experimental and control groups. The instrument used was an achievement motivation scale based on McClelland’s indicators. The results indicate that, before treatment, both groups exhibited low to moderate levels of achievement motivation. After three sessions of role playing, the experimental group demonstrated substantial improvements in academic responsibility, performance, courage, achievement drive, and self-confidence. A comparative analysis reveals an average increase of +17.10 in the experimental group, whereas the control group increased by only +2.65. Thus, the role-playing method is proven effective in enhancing students’ achievement motivation in the Islamic school context.   Keywords: Role Playing, Achievement Motivation, Learning Motivation, Islamic Education